The roles of experts in forest-related participatory processes in Europe - Su, Yu-Tzu (2019)
Demands for participatory processes in forest related decision-making have grown with the shift from government to new modes of governance. However, conflicts between participants occur due to that they hold different interests and expertise. There is uncertainty about the value and function of experts in participatory processes. There exist many studies of case studies of different participatory processes but few have had a focus on the role of experts in forest-related participatory processes. Thus, the aim of this study is to investigate the role of experts in forest-related participatory processes in Europe and explore what influence they bring into the phases of policy formulation and management planning. This study presents a systematic literature review of 30 articles published during year 2006-2018. Results indicate that experts’ values and functions are: Provision of knowledge-base; Supportive attitude towards participatory decision-making; Identified roles as facilitator, organiser and observer; Contribution of social contacts and network. Governmental experts from the top of the hierarchy are evident because the stage of policy formation focus on a future envision. And, in the management planning phase, experts primarily are requested to cooperate with local authority and professionals. Moreover, administratively based experts and scientists are the most identified types of experts. Especially, researchers are frequently recognised as facilitators when participatory processes are assisted by decision-support tools. Expert-facilitator play the multifunctional role to sort technical problems, advise in complex debates and bridge the relations among participants. During the coding process, the textual interpretation of identifying experts was time consuming due to inadequate explanation and description of the role. The suggestion for future research is a more detailed elaboration of the roles will result a better later analysis.